2009
DOI: 10.1111/j.1651-2227.2009.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal cholestasis: differentiation of biliary atresia from neonatal hepatitis in a developing country

Abstract: One-third of all NCS in India is due to BA and among the intrahepatic causes acquired infection and galactosaemia are common. Liver biopsy is the best method to differentiate NH from BA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
1
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 13 publications
6
39
1
8
Order By: Relevance
“…Hessel et al (15) reported that the sensitivity was 76% for liver biopsy in diagnosing extrahepatic cholestasis, with an accuracy of 86% for biopsy, rising to 96% when both tests (liver biopsy and ultrasound) were considered together. Poddar et al (22) reported that the liver biopsy was 100% accurate in differentiating BA from neonatal hepatitis. …”
Section: Discussionmentioning
confidence: 99%
“…Hessel et al (15) reported that the sensitivity was 76% for liver biopsy in diagnosing extrahepatic cholestasis, with an accuracy of 86% for biopsy, rising to 96% when both tests (liver biopsy and ultrasound) were considered together. Poddar et al (22) reported that the liver biopsy was 100% accurate in differentiating BA from neonatal hepatitis. …”
Section: Discussionmentioning
confidence: 99%
“…PFIC accounts for 3-13% cases of neonatal cholestasis syndrome (NCS) and accounts for 10-15% of children requiring liver transplantation (LT). [3][4][5][6][7] It has an estimated prevalence of 1 per 50,000 to 1 per 100,000 births although the exact prevalence is unknown. 1,8 PFIC 1 and 2 present in infancy or early childhood, whereas PFIC 3 can present at any age from infancy to adolescence.…”
Section: P Rogressive Familial Intrahepatic Cholestasis (Pfic) Ismentioning
confidence: 99%
“…3,13,14 La instalación de la ictericia en las primeras dos semanas, la persistencia de materias hipocólicas, los valores de BT mayores de 12 mg/dLy de BD mayores de 6,8 mg/dL presentaron buena sensibilidad para el diagnóstico de atresia biliar, pero baja especificidad (50% a 60%). 13 La hipocolia fue el signo con mayor sensibilidad (86%) y especificidad (76%). 13,14 El ser pequeño para la edad gestacional presentó mayor asociación con la hepatitis neonatal.…”
unclassified
“…13 La hipocolia fue el signo con mayor sensibilidad (86%) y especificidad (76%). 13,14 El ser pequeño para la edad gestacional presentó mayor asociación con la hepatitis neonatal. 13,14 La ecografía abdominal tiene baja sensibilidad, por lo que no permite descartar el diagnóstico de atresia biliar cuando su resultado es normal.…”
unclassified
See 1 more Smart Citation